Emerging nanocomposite biomaterials as biomedical adsorbents: an overview. Issue 5 (3rd July 2018) - Kyzas, George Z.; Deliyanni, Eleni A.; Matis, Kostas A.; Lazaridis, Nikolaos K.; Bikiaris, Dimitrios N.; Mitropoulos, Athanasios C.
Abstract: Biomedicine and pharmacy identify highly important scientific fields within the present time. However, increased advancements in these sciences have influenced the identification of increased levels in environmental degradation through pollution. Pharmaceutical production has influenced increased scientific and public concern regarding the increasing rate of pollution attributed to high levels of toxicological properties within the products. Pharmaceutical compounds are not fully removed through the integration of wastewater treatment plants (WWTP). This renders pharmaceutical compounds, municipal effluents together with hospitals as the major culprits in the development of the majority of the sources that enhance environmental degradation. A wide range of the compounds have been the identified within WWTP effluents, surface water together with ground and drinking water on a global scale. All above has influenced the research development in technological field developing new ways for efficient removal of pharmaceuticals from wastewater produced from the pharmaceuticals or biomedical industries. This situation may be altered through the utilization of adsorbents. Therefore more studies have been published investigating the use of nanocomposite biomaterials for removing the pharmaceutical compounds existing in biomedical effluents. Abstract :